Gamification with Codeathon for Productivity Toward Sustainable Development Goal 8 – Decent Work and Economic Growth - Tayal, Swati; Rajagopal, K (Brazilian Journal of Operations & Production Management, 2024)
Goal: This study aims to examine the Gamification application of Productivity with Codeathon, which can make employees more engaging at work. The growing presence of Information technology in the industry is increasing the demand for a skilled workforce and further making them productive. Gamification’s growing popularity among the industry and academicians is bringing new emerging forms that are beneficial to influence the user experience. However, there are many areas in which gamification has yet to benefit the user experience. The study analyzed the gathered data using confirmatory factor analysis, and the later section detailed the study analysis using a structural equation method. Design/Methodology/Approach: An online questionnaire gathered data from IT professionals to adopt the exploratory research, where respondents from Pune, India, were the study participants. The statistical approach adopted for this study was factory analysis followed by structural modelling with the help of tools such as IBM SPSS and Amos, which adds to the empirical Gamification contribution. Results: The study indicated a relationship between Gamification and Productivity among IT employees, where Autonomy was a mediator factor. Limitations of the investigation: This study primarily focused on the information technology sector among Generation Z and Y, but future research can explore other industries and countries. Practical Implications: Gamification encourages the participants’ motivation level, making them productive at work and bringing sustainability. Companies shall organize gamified events like Codeathon and encourage their employees’ participation, and therefore, the human resources team shall include it as part of their annual budget and planning. Originality/value: There is limited study in the Codeathon, and this research contributes by analyzing the Gamification aspects with Competition and Autonomy. It addresses the organization’s emerging need for productivity issues, making it one of the limited studies in the Gamification with Codeathon. As a result, this study addresses the sustainable development goal 8 to bring and attain sustainability for work.